Serial Ketamine Infusions for Treatment-Resistant Bipolar Depression - Diana K. Orsini; Sara Di Luch; George Tomlinson; Gabrielle F. M. Lovell; Shreya Vasudeva; Nelson B. Rodrigues; Danica E. Johnson; Alastair J. Flint; Cristian-Daniel Llach; Roger S. McIntyre; Rodrigo B. Mansur; Keyvan Karkouti; et al. (JAMA Psychiatry, 2026)
Importance Antidepressant efficacy of intravenous (IV) ketamine has been demonstrated in major depressive disorder; however, the efficacy and safety of ketamine for bipolar depression remain largely unknown, with limited data available in this specific population. Objective To evaluate the efficacy, safety, and tolerability of adjunctive IV ketamine compared with midazolam for treatment-resistant bipolar I or II depression (TRBD). Design, Setting, and Participants The Ket-BD study (Ketamine for Treatment-Resistant Bipolar Disorder) was an investigator-led, double-blind, midazolam-controlled randomized clinical trial conducted at 3 sites in Ontario, Canada, from July 2022 to November 2025. Participants included adult outpatients (aged 21-65 years) with a primary bipolar I or II disorder DSM-5 diagnosis with a current moderate to severe major depressive episode (Montgomery-Åsberg Depression Rating Scale [MADRS] score ≥21), having had at least 2 failed trials of evidence-based pharmacotherapies. Data were analyzed from November 2025 through February 2026. Interventions Participants were randomized 1:1 to receive 4 flexibly dosed 40-minute infusions over 2 weeks of either ketamine (0.5-0.75 mg/kg) or midazolam (0.02-0.03 mg/kg) adjunctive to a stable dose of at least 1 mood stabilizer or antipsychotic. Main Outcomes and Measures The primary outcome was change in depression symptom severity measured by the observer-rated MADRS score from baseline to end of treatment (day 14). Safety and tolerability were assessed with close evaluation for potential treatment-emergent mania, hypomania, mixed features, or psychosis. Results Of 68 randomized participants (mean [SD] age, 44.4 [11.8] years; 38 female [55.8%]), 63 were included in the final efficacy analysis as 5 participants withdrew (1 ketamine, 4 midazolam) before the primary end point. In the primary efficacy analysis, controlling for sex, bipolar type, and baseline MADRS, the mean MADRS score at day 14 was significantly lower in the ketamine group compared to the midazolam group (between-group difference = −7.3 points; 95% CI, −12.0 to −2.5; P = .003; Cohen d = 0.7). No cases of mania, hypomania, psychosis, or suicide attempts were observed in either group. One case of mixed features (subthreshold hypomanic symptoms) was observed in each group. After the first infusion, 31 of 66 participants (47%) correctly guessed treatment allocation. Conclusions and Relevance In TRBD, adjunctive IV ketamine was well tolerated and associated with significant antidepressant effects compared to midazolam. Trial Registration ClinicalTrials.gov Identifier: NCT05004896